Medipix detectors in radiation therapy for advanced quality-assurance. (January 2020) - Rosenfeld, Anatoly; Alnaghy, Saree; Petasecca, Marco; Cutajar, Dean; Lerch, Michael; Pospisil, Stanislav; Giacometti, Valentina; Schulte, Reinhard; Rosso, Valeria; Würl, Matthias; Granja, Carlos; Martišíková, Mária; et al.
Abstract: Spectroscopy-based photon-counting detector systems, Medipix, have many applications in medicine. Medipix detectors benefit from providing energy information as well as high spatial resolution. In this article, a review of Medipix detector technology applied to medicine and imaging techniques are presented. The technology has been used to develop quality assurance (QA) measurement devices in radiation-based treatments. A gamma camera system for radiotherapy has been developed to measure dose delivered to prostate treatments in real-time. The advantage of a high-resolution detector has been utilized in proton and heavy ion therapy for dose QA, measuring the charge particle spectra, and beam geometry for mini-beams. Applications in medical imaging using helium ion beams have been investigated to replace CT for ion beam radiotherapy. This technique provides many advantages over conventional CT such as high-resolution imaging and spectroscopy-based information for planning in helium ion treatments. The Medipix technology has shown it can be broadly applied in radiation and particle therapy applications for accurate QA as well as proving high-resolution imaging in medicine.